INT Issue 11: The Traction of Drawing CFP - Simmons, Laurence; Barrie, Andrew (Interstices: Journal of Architecture and Related Arts, 2009)
Interstices 11 Call for Papers The Traction of Drawing December 3, 2009 Manus Occulata in Andrea Alciato (1546) Emblematum libellus (inverted) Why raise the issue of drawing again? With the proliferation and maturation of digital technologies, what is the use of the hand and the traces it makes on clay, stone, wood or paper? This symposium seeks to examine the technologies of drawing – their marks, lines, scratches, furrows, incisions, touches, dots and dashes, inscriptions, string lines, stains and blotches; pencilled, inked, chalked, brushed, illuminated or erased on diverse grounds. What is made in the acts of drawing comes into being through the sapience of a facture, not through any Cartesian process of mathème. Conceived thus, drawing is wholly based on an intimate knowledge of material manifestations, within which tangible lines become carriers of fluid and invisible links that guide intangible thought. Pulling in pieces of geometry, geology, alchemy, philosophy, politics, biography, biology, mythology, and philology from alien territories, one should write and draw with hesitation, discovering the multiple aspects of graphesis, a generative graphic process understood in its slow making. The fruitful vagueness of graphesis comes from the ambiguity embodied in the Latin spell: nullo dies sine linea, where linea (line), a heuristic device, must be understood as a line of writing, as a line in a drawing, or as the pulling of a line on a construction site. Architecture results from their miscegenation: images are written and words are drafted; cultural events and material expressions cross. Graphesis is a course of actions, the factures which actualize future and past. The quality and selection of the ink’s luminosity, graphite’s fatness, watercolour’s lightness, tempera’s density, the screen’s pixellation, the flexibility or rigidity of supports … readers of the drawings indirectly see and savour them all. They foster “inferences from facture”, an extremely productive procedure. To consider an artefact in terms of its facture is to consider it as a record of its own having been made. Drawings’ signifying power is in the liturgy of their making, which generates an aura that can be intuited by maker and reader simply by casting a glance. Drawing as tool, technique and technology exteriorises the mind and emotions; it makes present the invisible. Drawing as a forecasting, predictive medium aims at a destination; it has a scope and end, it designates. Projecting, throwing forward orthogonal or oblique lines, it can sever, as in sections and plans. In draughting, as an act of thought, drawing seeks enactment: the making of lines which instruct further making in implementation. Or it translates: from drawing to building and building to drawing. In sketches, outlines, and studies we may pursue an allusive idea through the traction of lines. The formative force of an idea, emanating from the body as from the mind, seeks ever greater precision, often in successive drafts or erasures. Conversely, gestures, traces or tracks of the line can be eventful, punctuate flows like notation in music, or regulate flows like a programme or grammé. Issue 11 of Interstices: A Journal of Architecture and Related Arts will be devoted to the exploration of these issues for which we invite you to submit a paper for consideration. Submissions: Please submit your paper by 28 February 2010 to The Co-ordinating Editor, Interstices 11, Rafik Patel <rafik.patel@aut.ac.nz> Refereed papers must not exceed 5000 words (including endnotes; excluding bibliography), non-refereed full papers 2500 words, and reviews 1000 words (longer papers are only accepted in special circumstances and with prior negotiation). Please check the Notes for Contributors (http://www.interstices.ac.nz/previousfiles/NotesForContributors2009.pdf) for details regarding style, formatting, spelling, etc. We also invite submission of drawings, which are normally published in the non-refereed part of the journal. However, for this issue we are considering an alternative review process that would allow us to referee visual submissions. Negotiations about this process have just only started and Notes for Contributors are not yet available. We will inform you about progress if you register your interest. RafikPatel School of Art & Design AUTUniversity, City Campus WE Building, 27 St Paul St Auckland 1010 T: +64 9 9219999 extn: 8073 Why raise the issue of drawing again? With the proliferation and maturation of digital technologies, what is the use of the hand and the traces it makes on clay, stone, wood or paper? This symposium seeks to examine the technologies of drawing – their marks, lines, scratches, furrows, incisions, touches, dots and dashes, inscriptions, string lines, stains and blotches; pencilled, inked, chalked, brushed, illuminated or erased on diverse grounds.What is made in the acts of drawing comes into being through the sapience of a facture, not through any Cartesian process of mathème. Conceived thus, drawing is wholly based on an intimate knowledge of material manifestations, within which tangible lines become carriers of fluid and invisible links that guide intangible thought. Pulling in pieces of geometry, geology, alchemy, philosophy, politics, biography, biology, mythology, and philology from alien territories, one should write and draw with hesitation, discovering the mul-tiple aspects of graphesis, a generative graphic process understood in its slow making. The fruitful vagueness of graphesis comes from the ambiguity embodied in the Latin spell: nullo dies sine linea, where linea (line), a heuristic device, must be understood as a line of writing, as a line in a drawing, or as the pulling of a line on a construction site. Architecture results from their miscegenation: images are written and words are drafted; cultural events and material expressions cross. Graphesis is a course of actions, the factures which actualize future and past. The quality and selection of the ink’s luminosity, graphite’s fatness, watercolour’s lightness, tempera’s density, the screen’s pixellation, the flexibility or rigidity of supports … readers of the drawings indirectly see and savour them all. They foster “inferences from facture”, an extremely productive procedure. To consider an artefact in terms of its facture is to consider it as a record of its own having been made. Drawings’ signifying power is in the liturgy of their making, which generates an aura that can be intuited by maker and reader simply by casting a glance. Drawing as tool, technique and technology exteriorises the mind and emotions; it makes present the invisible. Drawing as a forecasting, predictive medium aims at a destination; it has a scope and end, it designates. Projecting, throwing forward orthogonal or oblique lines, it can sever, as in sections and plans. In draughting, as an act of thought, drawing seeks enactment: the making of lines which instruct further making in implementation. Or it translates: from drawing to building and building to drawing. In sketches, outlines, and studies we may pursue an allusive idea through the traction of lines. The formative force of an idea, emanating from the body as from the mind, seeks ever greater precision, often in successive drafts or erasures. Conversely, gestures, traces or tracks of the line can be eventful, punctuate flows like notation in music, or regulate flows like a programme or grammé. Issue 11 of Interstices 11: A Journal of Architecture and Related Arts will be devoted to the exploration of these issues in which we invite you to submit a paper for consideration. Submissions Please submit your paper by 28 February 2010 to The Co-ordinating Editor, Interstices 11, Rafik Patel rafik.patel@aut.ac.nz Refereed papers must not exceed 5000 words (including endnotes; excluding bibliography), non-refereed full papers 2500 words, and reviews 1000 words (longer papers are only accepted in special circumstances and with prior negotiation). Please check the Notes for Contributors (http://www.interstices.ac.nz/previousfiles/NotesForContributors2009.pdf) for details regarding style, formatting, spelling, etc. We also invite submission of drawings, which are normally published in the non-refereed part of the journal. However, for this issue we are considering an alternative review process that would allow us to referee visual submissions. Negotiations about this process have just only started and Notes for Contributors are not yet available. We will inform you about progress if you register your interest.